Investigating the Factors That are Associated With Teachers’ Intentions to Utilize Research in Remote Areas of Greece - Trikoilis, Dionysios; Papanastasiou, Elena C. (Frontiers in Education, 2021)
Teachers around the world, serving in remote areas experience professional isolation (Bouck, 2004). In addition to being geographically isolated, challenges to remote teaching include a lack of professional support (Ralph, 2002) and experience of social isolation. Yet, the utilization of educational research has the potential to alleviate this issue. Therefore, this study examines the interplay between the factors that can possibly explain the teacher’s intentions to use research for professional development purposes in remote schools in Greece. Based on the results of the Structural Equation Model that was examined, research attitudes had the strongest direct relationship to intending to use research for professional development purposes, although research skills also played a major role (directly, and indirectly) in this relationship.